Advancements in minimally invasive treatment of deltoid ligament injuries combined with distal tibiofibular syndesmosis injuries - Kun Liu; Xiaoyan Ji; Peng Su (BMC Surgery)
Abstract The deltoid ligament (medial collateral ligament) and the syndesmosis (a composite ligamentous structure at the distal tibiofibular junction) are critical for maintaining ankle stability. In cases of high-energy ankle fractures, these structures are often injured simultaneously, leading to instability and potential long-term complications such as post-traumatic arthritis. This review aims to explore advancements in minimally invasive techniques for the treatment of combined deltoid ligament and syndesmosis injuries, with a focus on optimizing surgical outcomes and reducing patient morbidity. Current treatment strategies primarily involve cortical screws for syndesmosis stabilization and anchor fixation for deltoid ligament repair. Recent innovations, such as bioabsorbable screws, suture-button devices with elastic micromotion, and syndesmotic plates, have demonstrated potential in improving biomechanical stability while minimizing complications. Furthermore, minimally invasive techniques, including arthroscopic repairs with suture anchors, as well as ligament reconstruction using autografts, allografts, or synthetic ligaments, are becoming increasingly popular. By incorporating these advancements, the field is moving toward more effective and patient-centered approaches to achieve anatomical and functional restoration under minimally invasive principles. Future research should focus on further validating these techniques and identifying the most effective strategies for complex injuries.